KURIKULUM BERBASIS CINTA DARI PERSPEKTIF PEMASARAN JASA PENDIDIKAN DI MTS DARUL HIKMAH PULAU BESAR - Candra, Maila; Ahmad Zainuri; Muslim Gani Yasir (STKIP Subang, 2026)
This study aims to analyze the implementation of a love-based curriculum from the perspective of educational service marketing at MTs Darul Hikmah. In the increasingly competitive landscape of Islamic educational institutions, schools are required not only to provide academic achievement but also to offer distinctive values that strengthen their institutional positioning. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, students, and parents. The findings indicate that the love-based curriculum is implemented through humanistic learning interactions, empathetic communication, persuasive disciplinary practices, and a family-oriented school culture. Teachers play a central role in building emotional connections with students, creating a supportive and comfortable learning environment. From a service marketing perspective, the values of love are reflected in the elements of people, process, and institutional image, which contribute to building trust and parental loyalty. The study concludes that a love-based curriculum functions not only as a pedagogical approach but also as a positioning strategy that enhances the competitiveness and reputation of the institution.